Uji Organoleptik Tempe dari Biji Gude (Cajanus cajan (L.) Millps.) dengan Berbagai Konsentrasi dan Lama Fermentasi - Faujiah Faujiah; Iwan Doddy Dharmawibawa; Baiq Mirawati (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Tempe is a traditional grain-based food that is in great demand by the people of Indonesia, because in addition to its relatively cheap price, its vegetable protein content is also quite high. The purpose of this study was to determine the quality of tempeh through organoleptic tests made from gude (Cajanus cajan (L.) Millps.) seeds with different concentrations and fermentation time. This type of research is a pure experiment. The research was carried out at the Biology Laboratory, FSTT, Mandalika University of Education. The experimental research design used a Randomized Block Design (RAK). Consists of two factors, namely: yeast concentration (K1 = 1.5%; K2 = 2%; and K3 = 2.5%), and fermentation time (F1 = 24 hours; F2 = 30 hours; and F3 = 36 hours ), with 3 replications to obtain 27 experimental units. Data collection techniques using organoleptic tests, which include: color, aroma, texture, and taste tests. Sampling for panelists using purposive sampling technique. Organoleptic test data were collected through the hedonic preference test, with a scale of 1-5, namely: 1 = dislike, 2 = neutral, 3 = somewhat like, 4 = like, and 5 = very much like. The data analysis technique used Analysis of Variance (ANOVA) with a significant level of 5%. Based on the results of statistical analysis concluded that the concentration of yeast and fermentation time had a significant effect on the color, aroma, texture, and taste of the gude seed tempeh produced.